(untitled) (Research Nepal Journal of Development Studies, 2025)
Labor migration from Nepal to other countries, along with the money sent back home, has become a really big deal for the rural areas economy. It’s a sort of the main way a lot of families get by, and it helps keep things steady for the whole country too. From the evidence from places like South Asia, especially Nepal itself as a developing spot, this synthesis that pulls together different parts. It covers stuff on how people spend that remittance money, ways it fights poverty, investments that actually build something productive, getting more folks into financial systems, and even how it changes things inside households. That last bit, the intra household dynamics, it seems a little tricky to pin down sometimes, but the findings tie into the others. Overall, it’s clear these flows are key indicators, though the full impact varies by region. The reviewed evidence suggests that remittances have consistent effects on household wellbeing through consumption smoothing and on expenditure on food security, education, health care, housing, and debt repayment. In Nepal, these welfare effects are even stronger in rural areas with fewer locally available jobs and reduced access to formal credit. Nevertheless, the review also identifies that productive investment in agriculture, small businesses, and income-generating activities account for only a limited share of income repatriated through remittances. Where productive use occurs, productive use seems to be highly dependent upon household characteristics, financial services provision, market conditions as well as institutional support and services. At the macro level, the evidence suggests that remittances play a significant role in promoting economic stability and foreign exchange availability but their ability to impact on structural change (unless accompanied by complementary policy and financial instruments) is limited. A synthesis further reveals considerable unmet needs in Nepal to be filled around the role of determinants of productive remittance use, intra-household decision-making processes, as well as the gendered effect and the effectiveness of remittance policy.